Conservation and sustainable uses of medicinal and aromatic plants genetic resources on the worldwide for human welfare - Barata, Ana Maria (2016)
Plants have been used since ancient times to heal and cure diseases and to improve the health and the wellbeing of the populations. Medicinal and aromatic plants still form the basis of traditional or indigenous health systems of the populations in most of the developing countries, as reported by the World Health Organization (WHO).As a result of the expanding interest in medicinal and aromatic plants, new income generating opportunities are opening up for rural populations. With many of the MAPs gathered from the wild, the recollection and sale of MAPs is providing a complementary source of income for many poor rural households.Currently, we are facing an incomparably growing pressure on plant populations in the wild due to the increasing commercial recollection, largely unmonitored trade, and habitat loss. Profound knowledge of the features of the (international) trade in botanicals (size, structure, streams, commodities, traded quantities and their origin) is (1) essential for assessing the trade's impact on the plant populations concerned; and (2) required for conservation concepts and measures which have to meet future supply and the provisions of species conservation.